The Effect Of Promotion And Service Quality On Buying Interest At Online Travel Ticket Applications - Susbiyantoro; Nurlia, Titim; Harjoko (Best Journal of Administration and Management, 2022)
This study aims to determine the effect of promotion and service quality on buying interest in online travel ticket applications during the Covid-19 pandemic. The research sample was 99 respondents obtained from online questionnaires distributed to respondents who made purchases on the Online Travel Ticket application. The sampling technique used is non-probability sampling. The questionnaires were distributed online via google form and the data processing used SPSS Version 25. The research model used was a descriptive research model that systematically and accurately described the factors studied. The data testing technique used in this research is the validity test with the calculated r value and the reliability test with Croncbach's Aplha, the data analysis used is linear regression analysis to test and prove the research hypothesis. The results show that promotion and service quality simultaneously have a positive and significant effect on buying interest with online travel ticket applications.